The Factors Of Professional Orientation For Secondary School Students In Lattakia Province - صيوح , لؤي; ميا , علي; الرفاعي , عبد الهادي; العشعوش , . أيمن; اسماعيل, عصام; غدير , . باسم; حيدر , عز الدين; اسماعيل, رولا; خليل, فادي; ناعسة , عبير; عيسى , جميل; صالح , غسان; et al. (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The purpose of the current study is to recognize the factors that influence the career attitudes among secondary students in Lattakia province. A descriptive approach is used to achieve this objective. And the study sample consisted of (2519) secondary students. The scale applied in the study is comprised of four dimensions: social factors, economic factors, personal factors, and other factors. Findings showed that the personal factors are the most influential factors on students’ career attitudes, followed by economic factors. The results have also indicated that the social factors don’t play a significant role in career attitudes of the secondary students in Lattakia province. With regard to gender differences, it was found that males are more affected by social and economic factors than females, while females are more affected by personal factors than males.